Hey I'm not really sure how to start out this problem. We have to prove that if a = b (mod n), then ac = bc (mod n) How exactly would I prove from a=b to ac = bc for this problem?
Follow Math Help Forum on Facebook and Google+
Hello, Originally Posted by BlakeRobertsonMD Hey I'm not really sure how to start out this problem. We have to prove that if a = b (mod n), then ac = bc (mod n) How exactly would I prove from a=b to ac = bc for this problem? You can go to the definition of the congruence : a=b (mod n) <===> there exists an integer k (positive or negative) such that a-b = kn so from that, if you multiply by c : ac-bc=kcn. Let k'=cn. Then ac-bc=k'n <===> ac=bc (mod n)
View Tag Cloud